1984
DOI: 10.4319/lo.1984.29.5.0949
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of detritus by the copepod, Acartia tonsa1

Abstract: Ingestion, survivorship, and growth experiments were conducted with the marine Calanoid copepod, Acartia tonsa, various concentrations of the diatom, Thalassiosira weissjlogii, and detritus derived from the macrophyte, Thalassia testudinum. Copepod ingestion rates of detritus increased with detritus concentration from ~50 to > 1,700 pg Celiter-I.Copepod survival in detritus suspensions was significantly greater than in filtered seawater controls. The instantaneous mortality coefficient, z, of A. tonsa was a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
2

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(104 citation statements)
references
References 44 publications
4
98
0
2
Order By: Relevance
“…ingestion was not continuous. Our observations and those of Roman (1984) suggest the hypothesis that satiation of a copepod is a function of the amount of utilizable nitrogen or energy in its food. Acartia tonsa, feeding on Thalassiosira weissflogii at concentrations from about 150 to 900.lrgC I-', became satiated near 300 pgC 1-l (Roman 1984, his Fig.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…ingestion was not continuous. Our observations and those of Roman (1984) suggest the hypothesis that satiation of a copepod is a function of the amount of utilizable nitrogen or energy in its food. Acartia tonsa, feeding on Thalassiosira weissflogii at concentrations from about 150 to 900.lrgC I-', became satiated near 300 pgC 1-l (Roman 1984, his Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The increased ingestion of pellets in the presence of Thalassiosira weissflogii (Table 5) is attributed to an increased capture rate as observed for beads in the presence of T. weissflogii (Table 6 ) . Detrital particles (the macrophyte Thalassia testudinum) were eaten at similar rates with or without diatoms by Copepodid Stage V and adult Acartia tonsa (Roman 1984). This similarity of rates is attributed to the size of most of the detritus particles being in the range from 8 to 12 pm Equivalent Spherical Diameter (Roman 1984).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Both species are common in coastal waters and a low clearance of fecal pellets may be an adaptation to optimize the intake of high quality food particles in an estuarine environment where non-living particles usually dominate the particulate matter available to copepods (Paffenhöfer & Van Sant 1985). Supporting this, Roman (1984) found that only 10% of a laboratory population of A. tonsa survived 7 d on a detritus diet and that eggs could not be reared to adults on detritus. Other copepod species such as Eucalanus pileatus, Temora stylifera, and Oithona similis may be better adapted to coprophagous feeding since they clear and ingest fecal pellets at high rates (Table 5, Paffenhöfer & Knowles 1979, Paffenhöfer & Van Sant 1985, González et al 1994a.…”
Section: Processes Governing the Clearance Of Fecal Pelletssupporting
confidence: 62%